Fabrication methods of 3D periodic metallic nano/microstructures for photonics applications. Issue 2 (26th July 2013) - Hossain, Md Muntasir; Gu, Min
<x xml:space="preserve">Abstract</x> Periodic metallic nano/microstructures have received a great a deal of attention in the photonics research community over the last few decades due to their intriguing optical properties. Three‐dimensional metallic nano/microstructures such as metallic photonic crystals, metamaterials, and plasmonic devices possess unique characteristics of tailored thermal radiation, negative refraction and deep subwavelength confinement of light. In this article, the recent progress on the experimental methods for the realisation of three‐dimensional periodic metallic and thin metal film coated dielectric nano/microstructures operating from optical to mid‐infrared frequencies has been reviewed. Advancement of the state‐of‐the‐art nanofabrication methods over the last few decades have led to the development of metallic nano/microstructures of diverse geometries, high resolution features and large scale production. The recent progress in the novel fabrication methods have inspired the development of functional and exciting photonic devices based on periodic metallic nano/microstructures with various applications in photonics including communications, photovoltaics, and biophotonics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>